Symbolic values, occupational choice, and economic development - Giacomo Corneo; Olivier Jeanne (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2007)
Channeling human resources into the right occupations has historically been a key to economic prosperity. Occupational choices are not only driven by the material rewards associated with the various occupations, but also by the esteem that they confer. We propose a model of endogenous growth in which occupations carry a symbolic value that makes them more or less attractive; the evolution of symbolic values is endogenous and determined by purposive transmission of value systems within families. The model sheds light on the interaction between cultural and economic development and identifies circum- stances under which value systems matter for long-run growth. It shows the possibility of culturally determined poverty traps and offers a framework for thinking about the transition from traditional to modern values.
Keywords: D1; O1; 330; symbolic values; occupational choice; economic development; long-run growth.; Bildungsverhalten; Kulturpsychologie; Soziale Werte; Entwicklung; Neue Wachstumstheorie; Theorie